Die "voorwetenskaplike" geskiedsbewussyn en "vroeë wetenskaplike" geskiedskrywing in die Nederduitsch Hervormde Kerk - Schoeman, P. R. (HTS teologiese studies, 2004)
The “prescientific” historical awareness and “early scientific” historical writing in the Nederduitsch Hervormde KerkThe scientific practice of Church History within the Nederduitsch Hervormde Kerk van Afrika commenced in 1920 with the submission of S P Engelbrecht’s doctoral thesis. The preliminary era can be typified as the “prescientific” historical awareness that started with an official “Pastoral Writing” by the Synod in 1855 and developed into the “early scientific” historical writing with the writing of Van Warmelo in 1881. This “early scientific” historical writing continued to develop until the early twentieth century. The aim of this article is to explore this era within the “Hervormde” church against the background of a reflection on the scientific nature of ecclesiastically historical research.